An Outbreak of Multi-drug Resistant Enterotoxigenic Escherichia coli (ETEC) Infection among Infants in a City of Southwest China, 2012 - Chen, Xi; W, Yuan; LJ, Zhang; Q, Li; ZD, Zhang; H, Wang; YJ, Sun (OSIR Journal, 2016)
Multi-drug resistant (MDR) diarrheagenic Escherichia coli has rapidly spread worldwide and represents the most serious threat to management of diarrhea in developing countries. We investigated an outbreak of severe diarrhea in a neonatal ward during 1 Apr-30 Jul 2012, where 60 suspected cases were found. To identify possible sources of infection, we conducted a case-control study through which we identified the increased infection risk of 4.6 fold for each liter of bottle milk feeding (OR = 4.6, 95%CI = 1.50-14.70). E. coli serotype O128:H45 with virulence gene stIb was found in 14 out of 18 stool or diaper swab samples and were MDR. This was a neonatal diarrhea outbreak caused by multi-drug resistant E. coli while bottle milk feeding was the possible vehicle in facilitating the transmission. This outbreak reinforces that enterotoxigenic Escherichia coli (ETEC) should be considered when the clinical picture is consistent and common gastrointestinal pathogens are not found.   Keywords: multi-drug resistant, ETEC, hospital-associated infections